La gestione delle emozioni e la crescita socio-emotiva nei fighters: una ricerca empirica sugli atleti di kickboxing della Federkombat - Flavia Verona (Eracle. Journal of Sport and Social Sciences, 2025)
Sport is a widespread educational practice involving over 200 million children and young people worldwide, fostering personal development and emotional management within a context of enjoyment and social relationships. An exploratory study conducted on Federkombat’s kickboxing athletes during the sporting year 2022-23 examined how they perceive challenges and failure—either as motivational stimuli or discouraging factor. Results show that these athletes, despite experiencing stress and anxiety in competitions, view challenges as opportunities for growth and personal improvement. Additionally, they demonstrate well-developed socio-emotional skills and participate in a sporting environment that balances sacrifice with satisfaction. Combat sports thus prove to be educational, promoting fun and positive relationships while debunking the stereotype of violent activities devoid of formative values.